1994
DOI: 10.1212/wnl.44.5.878
|View full text |Cite
|
Sign up to set email alerts
|

Specific learning disability in children with neurofibromatosis type 1

Abstract: To determine whether previously reported areas of increased T2 signal intensity on MRI examination in children with neurofibromatosis type 1 (NF 1) are associated with deficits in development and learning common in this population, we evaluated 51 children with NF 1 (aged 8 to 16 years). Forty children completed the full assessment protocol (MRI, medical, psychometric, speech therapy, and occupational therapy assessments). The mean Full Scale IQ scores for the entire study population showed a left shift compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
134
1
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(144 citation statements)
references
References 0 publications
6
134
1
3
Order By: Relevance
“…Brain manifestations include et al, 2005Brain manifestations include et al, , 2006North et al, 1994;Payne et al, 2011;Rowbotham et al, 2009;Roy et al, 2010). Social and behavioral problems include difficulties with social skills and communication, problems with forming friendships, rejection by peers, and social isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Brain manifestations include et al, 2005Brain manifestations include et al, , 2006North et al, 1994;Payne et al, 2011;Rowbotham et al, 2009;Roy et al, 2010). Social and behavioral problems include difficulties with social skills and communication, problems with forming friendships, rejection by peers, and social isolation.…”
Section: Introductionmentioning
confidence: 99%
“…While café-au-lait spots and neurofibromas are of mainly cosmetic significance, learning difficulties in children with NF1 may result in failure to achieve their full academic and social potential, and thus cause more serious problems , Dilts et al 1996, North et al 1997a). Previous studies have not revealed a specific profile of learning disabilities in children with NF1 (Eldridge et al 1989, Ferner 1994, Legius et al 1994, Moore et al 1994, Dilts et al 1996.…”
mentioning
confidence: 99%
“…Hofman and coworkers (1994) found that at least 30% of their patients with NF1 could be classified as having ADHD while their non-affected siblings did not. It has also been suggested that behavioural symptoms in children with NF1 may possibly meet the diagnosis of attention-deficit disorder without hyperactivity , North et al 1995.…”
mentioning
confidence: 99%
“…No. 4 and unpredictable, and in some instances can remit spontaneously. This will make it important to have data on natural history, lest spontaneous cessation of tumor growth be mistakenly attributed to the effects of a drug being tested.…”
Section: Outcomes Measurement In Clinical Trialsmentioning
confidence: 99%